The Decision Process of Purchasing Green Occupancy; an Investigation of Consumer Perceptions and Preferences - Widodo, Arry; Setyorini, Retno; Munadi Al Khairi, M. (International Journal of Engineering and Technology, 2018)
Every human being needs a house that is not only for shelter and family activity as well as a means of investment, but also required to accommodate the needs and desires of the owner such as, strategic location, good and sturdy building, and comfortable environment. In the development of residential choosing eco-friendly concept, PT. Ciputra Residence is one of the developers who are developing real estate and commercial area based on environmentally friendly. Population and household growth and supported by government regulations on residential concept that offer "green" building, will increase consumer perception and preference towards decent and comfortable occupancy. The concept of eco-friendly development can be a solution to understand the environment as a whole. Buildings built with the concept of environmentally friendly turns out to have more high selling value. This further proves to the people's awareness of the environment. Based on these problems, this study aims to determine the effect of consumer perceptions and preferences on the process of purchasing decision of green product (study at PT Ciputra Housing Citra Raya Tangerang).This research method is quantitative research with kind of causal description. The measurement scale used is Likert scale. The population of this research is the resident of Citra Raya Tangerang housing. The sampling technique used is Non Probability Sampling with Incidental Sampling type. Data analysis method used is Structural Equation Modeling (SEM).Based on the result of research can be concluded that consumer perception in good category, consumer preference in good category, decision process of purchase of green product occupancy in good category, and from result of SEM analysis that environment influence variable have significant influence to decision process of purchase of green product occupancy.Â Â Â